Expulsion of the Copper- T 380A intrauterine device inserted immediately after delivery and within 48 hours postpartum - Escudero, Francisco (2015)
OBJETIVE: To compare the rate of expulsion of intrauterine device (IUD) Copper T 380A inserted do postalumbramiento and within 48 hours after delivery. LOCATION: Department of Obstetrics Archbishop Loayza Hospital. MATERIALS AND METHODS: The study included 614 postpartum women who are TCu 380A IUD inserted after the birth or within 48 hours after birth, between 1992 and 1998. Statistical analysis was obtained frequencies, the test was applied chi square cumulative rates per 100 woman-years were determined using the life table. RESULTS: There were 176 IUD users postalumbramiento and 438 within 48 hours after birth. There was no significant difference between groups with respect to age, parity, marital status or previous use of contraceptive methods. Expulsion rates were higher at 3, 6 and 12 months follow-up users in whom TCu 380th dlu inserted within 48 hours postpartum (47.8, 49.6 and 55.3) compared to postalumbramienta. (20.1, 21.2 and 23.5), with statistically significant difference (p <0.0001). The expulsion was less common in large users multiparous, regardless of time of insertion (p <0.002). CONCLUSIONS: The rate of removal of DLU TCu 380A inserted after birth is lower in the postalumbramiento compared to 48 hours after birth and the expulsion of the IUD TCu 380A is lower if the users are large multiparous, regardless of the time of insertion.